Apple of Discord The "Hungarian Factor" in Austro-Serbian Relations, 1867-1881 - Armour, Ian D. (Purdue University Press, 2014)
This book focuses on the hitherto unexplored Hungarian influence on the Habsburg Monarchy's policy toward Serbia after the 1867 Ausgleich, and it argues that this early period was critical in shaping policy after 1871, down to the imposition on Serbia in 1881 of a system of economic and political control.